IMPLEMENTATION OF SHARIA PRINCIPLES IN THE PREPARATION OF FINANCIAL REPORTS: A CASE STUDY IN ISLAMIC BANKING - Darma (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to analyze the implementation of sharia principles in the preparation of financial statements in Islamic banking in Indonesia. Using a descriptive qualitative approach, this study highlights key challenges such as inconsistencies in the application of sharia accounting standards, lack of practitioners' understanding of sharia principles, and the need for harmonization between international and sharia standards. The results show that most Islamic banks have adopted sharia-based reporting models such as murabaha and mudharabah financing. However, there are still gaps in information disclosure and revenue recognition. The role of the sharia committee and the use of information technology have proven important in increasing transparency and accountability. This study recommends improving Human Resources (HR) training and strengthening sharia regulations to ensure the quality and compliance of financial statements with Islamic values.